Dampak Adaptasi Iklim terhadap Perempuan di Kiribati : Perspektif Keamanan Manusia - Feiby Anna Maria Luntungan; Nur Isdah Idris (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
The rise in sea levels caused by climate change has compelled island nations such as Kiribati to implement strategic policies, including climate adaptation, to address its impacts. This study employs a descriptive qualitative method with an analytical framework grounded in the theories of human security and ecofeminism to assess the effects of climate change adaptation strategies on women in Kiribati. Climate change has affected every aspect of human security—from economic conditions to personal safety—posing layered and disproportionate challenges for women, who often bear primary responsibility within the household. The study finds that women are not merely victims but also agents of change and drivers of climate adaptation through advocacy rooted in their lived experiences and environmental knowledge. This research underscores the importance of inclusive, participatory, and gender-just adaptation policies. Only through such approaches can climate crisis responses foster truly sustainable resilience across all sectors of society.